Sudan looks East China, India & the politics of Asian alternatives - Large, Daniel; Patey, Luke A. (Boydell & Brewer, 2011)
By successfully turning to China, Malaysia and India from the mid-1990s, amidst civil war and political isolation, Khartoum's 'Look East' policy transformed Sudan's economy and foreign relations. Sudan, in turn, has been a key theatre of Chinese, Indian and Malaysian overseas energy investment. What began as economic engagements born of pragmatic necessity later became politicized within Sudan and without, resulting in global attention. Despite its importance, widespread sustained interest and continuing political controversy, there is no single volume publication examining the rise and nature of Chinese, Malaysian and Indian interests in Sudan, their economic and political consequences, and role in Sudan's foreign relations. Addressing this gap, this book provides a groundbreaking analysis of Sudan's 'Look East' policy. It offers the first substantive treatment of a subject of fundamental significance within Sudan that, additionally, has become a globally prominent dimension of its changing international politics. Daniel Large is research director of the Africa Asia Centre, Royal African Society at the School of Oriental and African Studies, London, and founding director of the Rift Valley Institute's digital Sudan Open Archive. Luke A. Patey is a Research Fellow at the Danish Institute for International Studies
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1900-2000; Außenpolitik; Investments, Asian / Sudan; Außenwirtschaftspolitik; Asien; Sudan / Foreign relations / Asia; Asia / Foreign relations / Sudan; Sudan / Foreign relations / 20th century; Sudan / Foreign relations / 21st century; Indien; China; Sudan; Aufsatzsammlung